علاقة مستوى زنك المصل مع العد الشائع وشدته - الخير, عبد الله; خياط, محمد; رجب, علا (Latakia University Journal -Medical Sciences Series, 2019)
Background: Acne vulgaris is a chronic inflammatory disease of pilosebaceous unit occurring in adolescent age group. Zinc inhibits the growth of propionibacterium acnes and activates natural killer cells and phagocytic capacity of granulocytes. It also inhibits enzyme (5a - reductase) and suppresses sebaceous gland activity. Some investigators have reported an association between low serum zinc levels and acne vulgaris, while others have not found the same. Aim: this study aimed to compare serum levels of zinc in patients with acne vulgaris with its levels in control subjects without this disease, and to analyze the presence of a relationship between zinc status and the severity of acne. Materials and methods: This analytic observational case- control study included (93) patients with acne vulgaris and (85) control subjects without acne. Levels of serum zinc were determined using Atomic Absorption Spectrophotometry and each patient had a complete dermatological examination including global acne grading system (GAGS). Results: Mean serum level of zinc in acne patients and control was (100.8±18.5) mg/dl, (106.4±25.8) mg/dl, respectively. Although the mean serum zinc level was lower in acne group, it was not statistically significant (p- value=0.1).On the other hand, there was a significant inverse correlation between serum zinc levels and the severity of acne lesions. We observed that the serum zinc level in female patients was lower than its level in male patients and the difference was statistically significant. We also found that there was no correlation between serum zinc levels and each of duration of disease and the age of patients. Conclusion: The results of our study suggest that zinc levels may be related to the severity and the type of acne lesions in patients with acne vulgaris. Relative decrease of serum zinc level in acne patients suggests a role for zinc in the pathogenesis of acne vulgaris. مقدمة: العد الشائع هو مرض التهابي مزمن يصيب الوحدة الشعرية الزهمية ويحدث في سن المراهقة. يثبط الزنك نمو الجراثيم البروبيونية العدية وينشط الخلايا القاتلة الطبيعية وقدرة المحببات على البلعمة. كذلك يثبط أنزيم 5-ألفا ريدوكتاز ونشاط الغدد الزهمية. سجل بعض الباحثين وجود علاقة بين انخفاض مستوى الزنك المصلي والعد الشائع، بينما لم يجد باحثون آخرون النتيجة ذاتها. الهدف: هدفت دراستنا إلى مقارنة مستوى الزنك لدى مرضى العد الشائع مع قيمته لدى الأصحاء وإلى دراسة وجود علاقة بين شدة العد ومستويات الزنك المصلية. المواد والطرائق: دراسة تحليلية من نمط حالة – شاهد تضمنت (93) مريض عد شائع و (85) شاهد. تم قياس مستويات الزنك المصلية باستخدام طريقة المقايسة اللونية كما تم إجراء فحص كامل من الناحية الجلدية لكل مريض باستخدام نظام تصنيف العد العالمي .(GAGS) النتائج: سجلت دراستنا أن متوسط مستوى الزنك لدى المرضى (100.8 ± 18.5)ملغ/دل أما لدى مجموعة الشاهد فسجلت قيمة مقدارها 106.4 ± 25.8)) ملغ/دل وبالرغم أن مستوى الزنك الوسطي أخفض لدى المرضى مقارنة مع الشواهد إلا أن هذا الفرق لم يكن هاما إحصائيا مع قيمة (P- value=0.1) . بالمقابل لاحظنا وجود علاقة عكسية هامة بين مستوى زنك المصل وشدة الاندفاعات العدية.لاحظنا أيضا أن مستوى الزنك أخفض لدى الإناث المصابات بالعد مقارنة مع الذكور وكان الفارق هام إحصائيا. بينما لم نجد علاقة بين كل من مدة المرض والعمر ومستوى زنك المصل. الخلاصة: تقترح نتائج دراستنا أن مستويات الزنك يمكن أن تكون ذات علاقة مع شدة الاندفاعات العدية لدى مرضى العد الشائع وأن النقص النسبي للزنك لدى مرضى العد الشائع يمكن أن يقترح وجود دور للزنك في الآلية الإمراضية للعد.